The Effectiveness of Read, Cover, Remember, Retell Strategy towards Students’ Reading Comprehension - English Education FKIP (Juliet, 2020)
This research was conducted to find out whether using the Read, Cover, Remember, Retell strategy could have a significant effect on the reading comprehension of 11th grade students at SMK 3 Tanjungpinang. This research was conducted because the writer found several problems faced by students in SMK 3 Tanjungpinang. This research was a quasi-experimental design. The sample was 11th grade students in SMK N 3 tanjungpinang. The class was divided into 2 classes, the experimental class and the control class, the experimental class was treated using the Read, Cover, Remember, Retell strategy and the control class was given treatment using the Grammar Translation Method. From the results of this study, it was found that teaching students using the Read, Cover, Remember, Retell strategy was more effective then using the Grammar Translation Method.